Comparative Study of Variations in English Language Teaching Methode in Bilingual Elementary Schools - Shella Herliana; Honest Ummi Kaltsum (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2026)
Some elementary schools still apply conventional, teacher-centered methods in teaching English, which provide limited support for students’ active participation. This study aims to describe the variations of English language teaching methods in lower-grade classrooms, identify the challenges encountered in their implementation, and explain the solutions adopted by teachers. The research employs a descriptive qualitative method with a narrative approach, collecting data through interviews, observations, and documentation. Data analysis uses Spradley’s approach, including data reduction, data display, and conclusion drawing, with credibility ensured through prolonged engagement, triangulation, and member checking to validate the research findings. The results indicate that both schools implement varied and interactive teaching methods supported by digital tools; however, one school still predominantly relies on conventional methods such as lecturing. The main challenges include limited instructional time, students’ characteristics, and teachers’ mastery of teaching methods. The solutions involve the use of rewards, assessment modifications, learning applications, teacher training, and method differentiation. In conclusion, the implementation of English language teaching methods has become more varied and student-centered. The implication is that teachers and schools need to select and combine contextual, student-centered English teaching methods that align with bilingual learners’ characteristics to make learning more effective and meaningful.